High Cefepime Plasma Concentrations and Neurological Toxicity in Febrile Neutropenic Patients with Mild Impairment of Renal Function - Lamoth, F. (American Society for Microbiology (ASM), 2010)
High-dose cefepime therapy is recommended for febrile neutropenia. Safety issues have been raised in a recent meta-analysis reporting an increased risk of mortality during cefepime therapy. Cefepime-related neurological toxicity has been associated with overdosing due to severe renal dysfunction. This study aimed to investigate the association between cefepime plasma concentrations and neurological toxicity in febrile neutropenic patients. Cefepime trough concentrations (by high-performance liquid chromatography) were retrospectively analyzed for 30 adult febrile neutropenic patients receiving the recommended high-dose regimen (6 g/day for a glomerular filtration rate [GFR] of >50 ml/min). The dose adjustment to renal function was evaluated by the ratio of the cefepime daily dose per 100 ml/min of glomerular filtration. The association between cefepime plasma concentrations and neurological toxicity was assessed on the basis of consistent neurological symptoms and/or signs (by NCI criteria). The median cefepime concentration was 8.7 mg/liter (range, 2.1 to 38 mg/liter) at a median of 4 days (range, 2 to 15 days) after the start of therapy. Neurological toxicity (altered mental status, hallucinations, or myoclonia) was attributed to cefepime in 6/30 (20%) patients (median GFR, 45 ml/min; range, 41 to 65 ml/min) receiving a median dose of 13.2 g/day per 100 ml/min GFR (range, 9.2 to 14.3 g/day per 100 ml/min GFR). Cefepime discontinuation resulted in complete neurological recovery for five patients and improvement for one patient. A multivariate logistic regression model confirmed high cefepime concentrations as an independent predictor of neurological toxicity, with a 50% probability threshold at ≥22 mg/liter (P = 0.05). High cefepime plasma concentrations are associated with neurological toxicity in febrile neutropenic patients with mild renal dysfunction. Careful adherence to normalized dosing per 100 ml/min GFR is crucial. Monitoring of plasma concentrations may contribute to preventing neurological toxicity of high-dose therapy for this life-threatening condition.